On The Advantages of Piecemeal Integration: A model of trade with several countries where local integration benefits all - Bodil O. Hansen; Hans Keiding (Copenhagen Business School (CBS), Department of Economics, 2005)
For the study of economic integration, it is costumary to use a three countryworld, where two of the countries may introduce forms of closer economic cooperation. In the present model, we follow this tradition but put special emphasis on the role of credit and entrepreneurship. Our model is of the standard neoclassical type, with the addition that production takes time and is subject to uncertainty. Also, firms must use the financial system in order to buy inputs; the cost of credit may differ among countries and industries, reflecting their basic patterns of uncertainty. Following the Newbery-Stiglitz approach, we show that in such model we may exhibit cases of Pareto inferior trade and, in particular, Pareto inferior economic integration. More specifically, we show that integrating countries of very different economic size may give rise to adverse effects on welfare, whereas integration of countries with a more similar economic structure and size tends to have beneficial effects for the parties.
hdl:10398/7495
Keywords: F11; F15; F34; 330; trade; uncertainty; Pareto inferior trade; regional integration